Peran Audit Syariah Internal dan Eksternal dalam Kepatuhan Syariah pada Lembaga Keuangan Islam - Amelia, Yessica; Muhammad Rizal; Sri Utami Nurhasanah (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2024)
This study aims to examine the role of internal and external sharia audits in ensuring sharia compliance in Islamic financial institutions through a literature review. Based on the analysis of various previous studies, it was found that sharia audits, both internal and external, play a crucial role in maintaining adherence to sharia principles and improving transparency and accountability in Islamic financial institutions. Internal audits focus on operational and procedural oversight, while external audits provide an independent assessment of overall sharia compliance. However, the main challenges faced include the lack of consistent audit standards, limited training for sharia auditors, and legal uncertainties in Islamic finance practices. This study recommends the development of clearer standards and enhanced training for sharia auditors to improve the effectiveness of sharia audit implementation in Islamic financial institutions